Corneal changes following near work in myopic anisometropia. (1st December 2012) - Vincent, Stephen J; Collins, Michael J; Read, Scott A; Carney, Leo G; Yap, Maurice KH
Abstract Purpose To examine the symmetry of corneal changes following near work in the fellow eyes of non‐amblyopic myopic anisometropes. Methods Thirty‐four non‐amblyopic, myopic anisometropes (minimum 1 D spherical equivalent anisometropia) had corneal topography measured before and after a controlled near work task. Subjects were positioned in a headrest to minimise head movements and read continuous text on a computer monitor for 10 min at an angle of 25 degrees downward gaze and an accommodation demand of 2.5 D. Measures of the morphology of the palpebral aperture during primary and downward gaze were also obtained. Results The more and less myopic eyes exhibited a high degree of interocular symmetry for measures of palpebral aperture morphology during both primary and downward gaze. Following the near work task, fellow eyes also displayed a symmetrical change in superior corneal topography (hyperopic defocus) which correlated with the position of the upper eyelid during downward gaze. Greater changes in the spherical corneal power vector (M) following reading were associated with a narrower palpebral aperture during downward gaze (p = 0.07 for more myopic and p = 0.03 for less myopic eyes). A significantly greater change in J0 (an increase in against the rule astigmatism) was observed in the more myopic eyes (−0.04 ± 0.04 D) compared to the less myopic eyes (−0.02 ± 0.06 D) over a 6 mm corneal diameter (p = 0.01). Conclusions Changes in corneal topography following near work are highly symmetrical between the fellow eyes of myopic anisometropes due to the interocular symmetry of the palpebral aperture. However, the more myopic eye exhibits changes in corneal astigmatism of greater magnitude compared to the less myopic eye.